IEO Annual Report, 2007. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2008)
The IEO's latest Annual Report covers its activities during the financial year ended April 2007. It summarizes the most recent IEO evaluations of The IMF and Aid to Sub-Saharan Africa and IMF Exchange Rate Policy Advice. The report also presents messages that are common to many IEO evaluations and are particularly noteworthy as the IMF proceeds with the implementation of its Medium-Term Strategy. Other topics discussed include implementation of recommendations made in 2006 by the External Evaluation Panel of the IEO, ongoing projects, the identification of future evaluations, and summaries of follow-ups of past evaluations.